الأضرحة بمدينة تلمسان ـ دراسة نموذجية ـ - دحماني, ام الخير; مطروح, صبرينة (جامعة الوادي University of Eloued, 2017)
Humann intéressât since the préhistorique période, the construction of cimenteries, as I fond thème a variété of formats and Most notable, and graves cimenteries dubbed (analgésique), which Is about tables of stone Is made up of several rooms a height of between mètres and There mètres, alse fond formes the other Is a caves carved in the rocks, and the Most important of those used in the caves "mezzanine-covered roof", are to Be fond in various formes to the Egyptiens, which was characterized by volumineux pyramide and Terrace, is quitte similaire to that fond in the civilisation of Mesopotamia. Where it was built and huge private terraces of marble temples, which consists of three vehicle sections on top of each other, be square base underpinning the temple surrounded by columns strikethrough pyramid In the era Romans, it has found three types of shrines: the shrines in the form of cellars underground, and the tombs of commemorative round surrounded Bbwaik its ribbed ceiling, and pyramidal tombs that have been made to Rome after its occupation of Egypt, as we find shrines in buildings Persian before Islam, had taken the forms in the form of towers, is a small circular room covered ceilings Msenmh, to the advantage of the Syrian shrines, especially in the period between the sixteenth and the fourth BC form cube that surmounted by a small pyramidal roof, and the spread of this type in all of Aleppo and Antioch to care about the rulers and the population in the Maghreb East great interest in building shrines on the graves of saints and scholars, mystics The rulers, however, most of these shrines today are unknown history do not know the history of construction and in some cases even their personal defunct.
Keywords: الأضرحة، تلمسان